2006
DOI: 10.1073/pnas.0604711103
|View full text |Cite
|
Sign up to set email alerts
|

The plasma membrane Na + /H + antiporter SOS1 interacts with RCD1 and functions in oxidative stress tolerance in Arabidopsis

Abstract: The adverse effects of high salt on plants include Na ؉ toxicity and hyperosmotic and oxidative stresses. The plasma membrane-localized Na ؉ ͞H ؉ antiporter SOS1 functions in the extrusion of toxic Na ؉ from cells and is essential for plant salt tolerance. We report here that, under salt or oxidative stress, SOS1 interacts through its predicted cytoplasmic tail with RCD1, a regulator of oxidativestress responses. Without stress treatment, RCD1 is localized in the nucleus. Under high salt or oxidative stress, R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
175
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 227 publications
(186 citation statements)
references
References 31 publications
9
175
0
2
Order By: Relevance
“…It has previously been reported that rcd1 is involved in response to a number of abiotic stresses (Overmyer et al, 2000(Overmyer et al, , 2005Ahlfors et al, 2004;Fujibe et al, 2004Fujibe et al, , 2006Katiyar-Agarwal et al, 2006). The rcd1-3 allele behaves similarly to the previously described alleles by displaying increased resistance to chloroplastic reactive oxygen species (ROS) induced by paraquat (Table I).…”
Section: Rcd1 and Sro1 Both Function In Abiotic Stress Responsesupporting
confidence: 51%
See 2 more Smart Citations
“…It has previously been reported that rcd1 is involved in response to a number of abiotic stresses (Overmyer et al, 2000(Overmyer et al, , 2005Ahlfors et al, 2004;Fujibe et al, 2004Fujibe et al, , 2006Katiyar-Agarwal et al, 2006). The rcd1-3 allele behaves similarly to the previously described alleles by displaying increased resistance to chloroplastic reactive oxygen species (ROS) induced by paraquat (Table I).…”
Section: Rcd1 and Sro1 Both Function In Abiotic Stress Responsesupporting
confidence: 51%
“…We independently isolated a T-DNA insertion allele of RCD1, rcd1-3, which has previously been described (Katiyar-Agarwal et al, 2006). This allele can be complemented by a 35S::RCD1 transgene (see Fig.…”
Section: Identification Of Mutations In Rcd1 and Sro1mentioning
confidence: 99%
See 1 more Smart Citation
“…5 Both EM reconstruction of SOS1 show that the cytosolic moiety forms an elongated structure that extends about 50 Å away from the TM domain. In this sense, the overall shape and size of the cytosolic moiety is extended enough to serve as a docking site for the regulatory SOS2 5 and MPK6 9 kinases and also to other proteins such as RCD1 10 thus, merging different stress signals. However, the volume of this region in the class 1 reconstruction is consistent with the size of the SOS1 cytoplasmic domain while the class 2 reconstruction displays smaller size.…”
Section: Discussionmentioning
confidence: 99%
“…9 In addition, it has been shown that SOS1 interacts with RCD1 and functions in the oxidative stress response. 10 These findings suggest that a variety of protein-protein interactions with the SOS1 cytosolic domain regulate its function. This would imply that SOS1 represents a central hub coordinating different stimuli in response to different stress signals, thus, constituting an important target for biotechnological applications.…”
Section: Introductionmentioning
confidence: 95%